2020
DOI: 10.1177/1687814020967580
|View full text |Cite
|
Sign up to set email alerts
|

Multi-response optimization for Nimonic alloy miniature gear fabrication using wire electrical discharge machining

Abstract: Generally, gear is an essential component in various electro-mechanical devices, but its manufacturing at the micro-level is challenging. The non-conventional manufacturing processes, such as electro-discharge machining (EDM), is suitable in gear fabrication. Although miniature gears have strict accuracy requirements, the optimization of the EDM process parameters, especially for advanced materials and alloys, is critical. In this paper, Nimonic alloy miniature gears are manufactured using wire-EDM and the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The surface roughness reduces from 500 rpm to 1000 rpm, and after that increases with a rise in speed, which is due to the developed wear on a machined surface with high spindle speed [65,66]. The surface roughness increased with feed rate due to strain hardening effect while machining with a higher feed rate [67,68]. Surface roughness is also enhanced with a higher depth of cut due to large volume removal from the surface, which generates the rough surface of the machined sample.…”
Section: Resultsmentioning
confidence: 99%
“…The surface roughness reduces from 500 rpm to 1000 rpm, and after that increases with a rise in speed, which is due to the developed wear on a machined surface with high spindle speed [65,66]. The surface roughness increased with feed rate due to strain hardening effect while machining with a higher feed rate [67,68]. Surface roughness is also enhanced with a higher depth of cut due to large volume removal from the surface, which generates the rough surface of the machined sample.…”
Section: Resultsmentioning
confidence: 99%
“…al. (36) studied the WEDM, which was used to manufacture nimonic alloy tiny gears. The effects of wire tension, T ON , and dielectric fluid on the variables of response were also investigated.…”
Section: Materials Removal Ratementioning
confidence: 99%
“…The comparative analysis revealed that the Bee Colony Cuckoo Search optimization method was superior to RSM. Chaudhary et al [119] analyzed the process parameters of WEDM viz., IP, T off , T on , wire tension, and dielectric fluid on the responses viz., SR, machining time, MRR, kerf width, surface micro-hardness, and depth of microhardness using Entropy-TOPSIS and Pareto ANOVA techniques. It was concluded from the analysis that dielectric fluid (60% of demineralized water + 40% Ethelene glycol), IP 3 A, T off 2 ms, wire tension 6 N, and T on 15 ms were the optimum values of influencing parameter (in the order) for better machining performance.…”
Section: Singh and Misramentioning
confidence: 99%